1996
DOI: 10.1111/j.1432-1033.1996.0691p.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA Ligase from the Fungus Coprinus cinereus

Abstract: ) -EJB 95 2128/4 DNA ligase was highly purified from the fungus Coprinus cinereus at the meiotic recombination stage, pachytene. The pachytene DNA ligase showed three polypeptides with molecular masses of 88, 84 and 80 kDa, as estimated by the [-"PIAMP-labeling assay. These three polypeptides were susceptible to reaction with an mAb against a 16-amino-acid sequence in human DNA ligase I, which is conserved in C-terminal regions of mammalian, vaccinia virus and yeast DNA ligases. Since rapidly purified prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The typical intracellular concentration of ATP is around 1-3 mM (32), indicating that the main fraction of nucleotide is present in the mono-magnesium-coordinated form. From the values shown in Table III, the intracellular concentration of the di-magnesium-coordinated ATP can be estimated as 60 -170 M, which is either higher or in the order of the K m of many ATP-dependent enzymes, including T4 DNA and RNA ligases (20,(33)(34)(35)(36)(37)(38)(39). It has been shown that the monomagnesium-coordinated form of ATP exists in aqueous solution as a mixture of rapidly exchanging mono-, bi-, and tridentate structures, with ␤-and ␥-phosphoryls being the main ligands (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The typical intracellular concentration of ATP is around 1-3 mM (32), indicating that the main fraction of nucleotide is present in the mono-magnesium-coordinated form. From the values shown in Table III, the intracellular concentration of the di-magnesium-coordinated ATP can be estimated as 60 -170 M, which is either higher or in the order of the K m of many ATP-dependent enzymes, including T4 DNA and RNA ligases (20,(33)(34)(35)(36)(37)(38)(39). It has been shown that the monomagnesium-coordinated form of ATP exists in aqueous solution as a mixture of rapidly exchanging mono-, bi-, and tridentate structures, with ␤-and ␥-phosphoryls being the main ligands (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome translocations are common in C. cinereus (176,301,392,541). Reciprocal translocations have been mapped between chromosomes 3 and 5 and between chromosomes 1 and 9 (176,392).…”
Section: Developmental Processes In the Basidiamentioning
confidence: 99%
“…The deletions led to an in-frame fusion of the HD2 gene a2 from the a gene pair with variable parts of the HD1 gene d1 from the d gene pair. In consequence, covalently linked proteins are formed whose components normally do not interact with each other (12,13,259,301,378). Interestingly, both former N-terminal domains become superfluous in such HD1-HD2 fusion proteins, consistent with their function in recognition and discrimination (13,259).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 99%
“…Assays of DNA ligase activity were performed as described previously (Matsuda et al, 1996;Teraoka et al, 1993) with minor modifications. Adenylation was performed in a 20 ml reaction mixture containing 60 mM Tris/HCl (pH 7?8), 10 mM MgCl 2 , 5 mM DTT, 50 mg BSA ml 21 and 1 mCi [a-32 P]ATP (3000 Ci mmol 21 ; 110 TBq mmol 21 ) and 2 ml of the ligase fraction.…”
Section: Methodsmentioning
confidence: 99%
“…NaPP i treatment was performed in the presence of 0?5 mM NaPP i in the reaction buffer. DSB ligation reactions were performed using a linearized pUC119 DNA with BamHI or SmaI as described previously (Matsuda et al, 1996).…”
Section: Methodsmentioning
confidence: 99%